"Discover and Explore": Creating Impactful STEAM Learning Experiences for Museum Professionals. (6th August 2019) - Saraniero, Patricia; Kelton, Molly L.
Abstract: Projects that blend Science, Technology, Engineering, Arts, and Mathematics (STEAM) can present a number of challenges, including the integration of disparate concepts or ideas. Weaving the arts together with mathematics and the sciences for museum visitors in meaningful ways is currently an area of development for many museum professionals. This article examines five essential elements for museum professionals' learning and development. These elements are examined through a case study of a professional development program designed to support museum professionals to collaboratively develop STEAM programming and exhibits. Drawing on this research, recommendations for future learning opportunities are offered.